Nucleosomal DNA sequence-dependent properties, targeting by novel platinum-intercalator compounds, and interactions with the p53 transcription factor - Chua, Eugene Yue Dao (2015)
DNA in the context of chromatin encodes the instructions for life, and in eukaryotic cells is packaged by histone proteins, together with other nuclear factors. The fundamental repeating unit of chromatin is the nucleosome, which packages DNA and regulates its accessibility by transacting factors. In this thesis, we investigate three research questions surrounding the nucleosome, namely, how DNA sequence affects nucleosome positioning and affinity, the impact of nucleosome targeting by platinum-intercalator compounds, and how nucleosome formation influences p53 binding to its recognition element. The anisotropy of DNA bending together with histone-specific interactions contribute to the sequence dependency of nucleosome stability and positioning, though the lack of structural information with a high affinity sequence has precluded a complete understanding of the mechanics of nucleosome positioning. We present here the crystal structure of a strong positioning and high affinity derivative of the Widom 601 sequence, 601L. By comparing the structural and biochemical properties of nine nucleosome core constructs with varying sequences and affinities, a mechanical model of DNA sequence-dependent behavior in the nucleosome is developed. DNA-damaging anticancer therapeutics are limited by toxic side effects and drug resistance. Given the chromatin context through which platinum anticancer therapeutics elicit cytotoxicity, the structural and dynamic properties of the nucleosome offer unique and relevant targets for anticancer drug design. We designed two novel platinum-intercalator compounds that successfully target a highly deformed DNA site near the nucleosome center. Both isomers are more cytotoxic to cancer cells than cisplatin, though one isomer forms interior nucleosomal adducts much more efficiently, leading to a more rapid and distinct impact on cell death. This reveals the impact of nucleosomal adduct location and drug composition on cellular responses, and presents new avenues for drug development. The transcription factor p53 is the central player in the cellular response to DNA damage and functions by activating gene expression leading to repair of the damage, or apoptosis in the event of severe insult. The importance of the chromatin context on p53 function has only been recently appreciated, and many functional details remain unclear. We leverage on our nucleosome positioning and stability platform to produce nucleosome core constructs containing a p53 recognition element. Affinity measurements of p53 binding to DNA and nucleosome core are revealed, which together with kinetic information uncover a potentially novel function of the p53 transactivation domains. This study and platform provides a more complete understanding of p53 function in chromatin. The study of chromatin form and function leads to greater understanding of the fundamental cellular processes that give rise to life. In this thesis, we make use of a variety of techniques to investigate various aspects of nucleosome structure and function, and so add to our rapidly-growing knowledge of chromatin biology.